Progresses in Fluid Inclusion Synthesis in Quartz - Jun Du; Honglun Chang; Hongwei Liu (Geofluids)
High-temperature and high-pressure (HTHP) fluids are one of the most extensive participants in geological events. The representative in situ sampling of the HTHP fluids, which is an essential prerequisite for precisely characterizing the HTHP fluids (including compositional and volumetric properties), has been a vital challenge. The technique of fluid inclusion synthesis (FIS) in quartz is one of the only options. It has experienced an almost 40-year development since the standard fracture healing method was invented. Considerable advances in our understanding of physicochemical properties of geological fluids and their roles in many geological processes have been achieved by the use of the FIS techniques. A set of methodologies for fluid inclusion synthesis have been established. Great progresses have also been made, which includes the various pretreatment FIS techniques, the in situ fracturing FIS technique closely associated with the HTHP apparatus, the in situ fracturing refilled FIS technique for large fluid inclusion synthesis at controlled time under unfavorable conditions, and the novel fluid inclusion synthesis by fused silica capillary. Such great many progresses of the quartz FIS techniques have been scattered in the geochemists’ individual research work, and systematic collection and objective evaluation are missing. Consequently, we synthesize existing research, describe and identify the basic operations, discuss the methodological issues like pros and cons, and highlight the problems and prospects of the quartz FIS techniques. Furthermore, it is suggested that in situ and (or) large volume fluid inclusion synthesis will be an important future direction in view of the growing applications of the FIS techniques in combination with microanalytical techniques, especially the Laser Ablation-Inductively Coupled Plasma-Mass Spectrometry (LA-ICP-MS). Our review would provide technical guidance to those who wish to investigate HTHP fluids and be beneficial to the future development and applications of the FIS techniques.